AP1G2 Affects Mitotic Cycles of Female and Male Gametophytes in Arabidopsis - Zhou, Yongmei; Fang, Wenqin; Pang, Ziqin; Chen, Li-Yu; Cai, Hanyang; Ain, Noor-Ul-; Chang, Men-Chi; Ming, Ray (Frontiers in Plant Science, 2022)
During sexual reproduction in flowering plants, haploid spores are formed from meiosis of spore mother cells. The spores then undergo mitosis, develop into female and male gametophytes, and give rise to seeds after fertilization. We identified a female sterile mutant ap1g2-4 from EMS mutagenesis, and analyses of two T-DNA insertion mutants, ap1g2-1+/- and ap1g2-3-/-, and detected a partial female and male sterility. The ap1g2 mutant gametophyte development was arrested at one-nuclear stage. Complementation test using a genomic sequence of AP1G2 with its native promoter restored the function in the three ap1g2 mutant lines. Transcriptome profiling of ap1g2 ovules revealed that four genes encoding clathrin assembly proteins PICALM5A/B and PICALM9A/B which were involved in endocytosis were down-regulated, which were confirmed to interact with AP1G2 through yeast two-hybrid assays and BIFC analysis. Our result also demonstrated that RALFL4-8-15-19-26CML16, and several calcium-dependent protein kinases including CPK14-16-17 were all down-regulated in the ovules of ap1g2-1+/-. Moreover, Ca2+ concentration was low in impaired gametophytes. Therefore, we proposed that through interaction with PICALM5A/B and PICALM9A/B, AP1G2 may mediate gametogenesis accompanied by Ca2+ signaling in Arabidopsis. Our findings revealed a crucial role of AP1G2 in female and male gametogenesis in Arabidopsis and enhanced our understanding of the molecular mechanisms underpinning sexual reproduction in flowering plants.